Estimation of thyroid gland volume using ultrasonography and its relation to anthropometric measurements in a population of northern part of West Bengal - Suchismita Ghosh; Anushree Das; Alipta Bhattacharya; Ratnadeep Poddar; Anirban Sadhu (Al Ameen Journal of Medical Sciences)
Background: Anthropometric data and thyroid gland volumetric analysis has been previously correlated with varying results and hence this study focusses on strengthening those data among the population of Northern part of West Bengal .Objectives: Assess the thyroid volume in different aspects (total thyroid volume, volume of right and left lobes individually) and gather various anthropometric and demographic data from study population. Establish significant correlation between the study parameters, if any. Methods and Material: Thyroid volumetric analysis was done using Ultrasound guidance and anthropometric data were collected following standardised protocols with the help of appropriate tools. Demographic data were collected using pre-formed and pre-tested questionnaire. Results: Volume of thyroid gland was found to be correlated with Body Surface Area, height, and weight of an individual. Additionally, there was significant sexual dimorphism in thyroid volume and right lobe of thyroid was more voluminous than the left one. Conclusions: Complexities of anthropometric relationship with thyroid volume has been a topic of interest for ages. Further correlations need to be searched with other demographic parameters like iodine consumption, ethnicity, and socio-economic status of an individual.